Religiosity among Muslims: a scale development and validation study - Mohd Mahudin, Nor Diana; Noor, Noraini M.; Dzulkifli, Mariam Adawiah; Janon, Nazariah Shar'ie (Universitas Indonesia, 2016)
While religiosity as a field of inquiry has been gaining research interest in recent years, a central issue about its conceptualisation, measurement, and relationships with work outcomes remains unresolved. The aims of this paper are: (1) to introduce a new scale designed to measure religiosity among Muslims, based on an Islamic perspective that centres on the bodily action or human activity (islam), the mind or understanding of God (iman), and the spirit or actualisation of virtue and goodness (ihsan); and (2) to demonstrate how religiosity relates to various work outcomes. We followed a rigorous multi-steps scale development procedure using four empirical studies involving 703 participants. The final scale yielded one factor with 10 underlying items. Our results showed that religiosity was positively correlated with job satisfaction, positive work behaviour, workplace integrity, and organisational commitment, but negatively correlated with antagonistic work behaviour. This new scale also showed incremental validity over an existing Muslim attitude scale in predicting organisational commitment and integrity. Overall, this new scale demonstrates good psychometric properties and is a promising tool for the measurement of religiosity among Muslims in organisational settings.